Representation of Superheroes in The Character of Alana in The Film Sri Asih - Dedy Arpan (ULTIMART Jurnal Komunikasi Visual, 2023)
Sri Asih, the first superhero character in Indonesia created in 1954 by R.A Kosasih in comic media, has undergone several adaptations in comics and films with different character variations and story backgrounds. In 2022, Jagat Sinema Bumilangit re-adapted the Sri Asih film using a different approach. The film introduces a new main character named Alana and presents a storyline adapted to the current context. This research purpose is to analyze the representation of superheroes manifested in Alana’s character in the Sri Asih film 2022. The study employs a descriptive qualitative approach and refers to Roland Barthes' theory to uncover the meanings of denotation, connotation, and myth within the Sri Asih film. The research findings reveal 10 scenes that represent superheroes through the character of Alana. The results provide insights into how superheroes are portrayed through the character of Alana in the Sri Asih film. Additionally, the study uncovers the presence of heroic myths in the visual narrative structures of the film. These findings contribute to understanding the adaptation of superhero characters and how they remain relevant to popular cultural trends, attracting fans from generation to generation. Keywords: representation; superhero; sri asih; film; barthes; myth